Kembalinya Barata Kulisusu: Kebangkitan Identitas Kelompok Bangsawan Kulisusu Dalam Proses Pemekaran Kabupaten Buton Utara - Nurlin, Nurlin (ETNOSIA : Jurnal Etnografi Indonesia, 2016)
AbstractThe expansion of a new autonomous region (DOB) not only provides an arena for reproductivepower of local elites, such as politicians, senior bureaucrats and businessmen, but also providesan access for the adatleaders to reaffirm the symbol of power attached to their heritablenobility. This article aims to explain the process of reproductive powers of Kulisusu aristocraticin the expansion process of North Buton regency. The reproduction of identity and power ofKalisusu royalty in the expansion process of North Buton begun since adat leaders got involvedin the expansion of political activities in order to legitimize the emergence of North Butonidentity. To legitimize North Buton identity, adat leaders are supported by the claims that theyhave genealogical relationship with their ancestors, the founders of Kalisusu royal nobility. Theinvolvement of adat leaders is, in fact, not on their own initiative, but by the expansion agents.However, the involvment of adat leaders have precisely giventhem a space for reproductivepower in a new autonomous regions, North Buton. It shows how the reproduction of identity isclosely associated with theirfuture interests. The study also found that the return of the rule ofKulisusu aristocratic into a new contestation isaimed to find the foundation of original Kalisusuadat.Keywords: identity reproduction, power, barata, contestation, autonomous.